Strategi Pemasaran Klinik Mata KMU Gresik Seabagai Pelayanan Kesehatan Mata - Leny Damayantie; R. Zainul Musthofa (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2022)
KMU Gresik Main Eye Clinic is a medical eye health service with modern technology that specifically deals with eye problems such as cataracts, glaucoma, cornea, retina and refraction. The trend of eye clinics is increasing, so marketing activities are a management tool in today's business world. With the development of existing eye clinics, the eye clinic marketing strategy has become competitive. The dynamics of competition in seizing market opportunities are becoming tighter and increasingly felt. Each eye clinic has a different promotion strategy, namely in conveying information about products related to the services available. The formulation of this research problem consists of: 1. What are the marketing strategies being carried out by the KMU Gresik eye clinic in 2020 – 2023? 2. What innovative ideas can researchers provide to increase the target offering of KMU Gresik eye clinic services in 2023? This study aims to find out the marketing strategy carried out by the KMU Gresik eye clinic in 2020 – 2023. As well as provide ideas for innovation in the KMU Gresik eye clinic so that it is easy to achieve the target of eye health services. The research method used in this study is a qualitative research method with a descriptive approach. The research instruments used to collect data are observation, interviews, and documentation. The marketing strategy carried out by the KMU Gresik Eye Clinic is the first before sales (stakeholder visits, Education, Screening, Home visit, KMU Goest to school). The second is sales (health services at clinics, diagnostic examinations, doctor's examinations, medical procedures or outpatient care). The third is after sales (control reminders for post cataract surgery patients one day, one week, and one month.